Investigating the Status of Women's Education Under Taliban Rule - Amiri, Mir Hussain; Ahmadi, Benafsha (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2023)
Education is one of the most basic and obvious needs of a society, which plays a significant role in human progress and development. It empowers people intellectually and spiritually and leads to improvements, innovations and discoveries. In Afghanistan, especially after the formation of the interim government, significant progress has been made in education. However, challenges remain, including the gender gap in education. While measures have been taken, the participation of girls in schools and universities, especially in rural areas, is low due to cultural and traditional restrictions. In the past, the Taliban has caused irreparable damage to the Afghan education system, especially for girls. In both periods of the Taliban, women were deprived of education and work. which had negative consequences for the economic and social status of women. In education, there remain important obstacles, including gender inequalities and the influence of the Taliban regime, to ensure fair access to education and empower Afghan youth. This qualitative research seeks to find an answer to how the Taliban government affects the rights of girls in education, examining their policies and practices, as well as other factors affecting women's lack of access to education in Afghanistan. In addition, effective strategies to solve these challenges will be examined. To support women's education, it is necessary to use multi-faceted approaches with the participation of different stakeholders, to challenge the ideologies of the Taliban, impose restrictions, increase awareness and the importance of women's education in society, and to provide suitable solutions for women's education.